Labor : one woman's work - Afsari, Mary Fariba (Avid Reader Press, 2026)
"A powerful memoir of medicine, identity, and family secrets froman esteemed ob-gyn as she unravels her grandmother's mysterious death while reimagining women's health care from a mobile clinic-for readers of The Beauty in Breaking and The In-Between. In Labor: One Woman's Work, Dr. Mary Afsari takes us on a deeply personal and transformative journey through her life as an ob-gyn. Set against the vivid backdrops of Portland, Oregon, and Shiraz, Iran, this powerful memoir intertwines the complexities of her professional life with the hidden truths of her family's past, exploring the intersection of medicine, identity, and the enduring search for agency. The story begins in the bustling corridors of an Oregon hospital, where Mary dedicates herself wholeheartedly to her patients-often at great personal cost. At the same time, Mary uncovers a long-buried family secret: the tragic story of her grandmother Mehry's death in 1950s Iran. This revelation propels her on a quest to untangle the threads of her family's history while confronting the forces that have shaped her identity and her professional mission. As Mary struggles with the oppressive realities of the medical-industrial complex and the growing attacks on women's reproductive rights, she chooses a path of bold defiance. Inspired by her grandmother's legacy and her own commitment tocompassionate care, she decides to take her work out of the hospital and on the road: she converts an RV into a mobile women's health clinic. This innovative act allows her to deliver personalized, critical reproductive health care services across the Pacific Northwest, creating community and enduring friendships along the way. "When women don't have a choice, bad things happen," Mary writes. Labor is anintimate, immersive personal story, a rallying cry in a post-Roe world, and an inspiring example of what women can do when they do havea choice. Rich with the voices of her patients and the vibrant cultural threads of her Iranian heritage, Mary's story challenges us to rethink the boundaries of health care and reclaim the autonomy of women's bodies and lives. With warmth, insight, and humor, Labor ultimately offers a vision of transformation, resilience, and the power of reclaiming one's path and saving other people's lives in the process"--